Reflective Approaches to European Governance
XI, 262 p.
Keywords: Celebrating the existence of contending theories of European integration, the book begins with a critical exploration of the concepts and theories used to examine this unique policy, presenting theoretically informed, empirical studies of the origin of the key themes of European governance, territorial politics, domestic-European linkages and the EU's foreign policy affairs.